Atmospheric temperature effect on Cosmic Ray count rate observed at Syowa Station in Antarctic - Kato, Chihiro; Kihara, Wataru; Ko, Yukino; Kadokura, Akira; Kataoka, Ryuho; Munakata, Kazuoki (2019)
The Tenth Symposium on Polar Science/Special session: [S] Future plan of Antarctic research: Towards phase X of the Japanese Antarctic Research Project (2022-2028) and beyond, Tue. 3 Dec. / Entrance Hall (1st floor) at National Institute of Polar Research (NIPR) conference object